Cesium-doped Dion-Jacobson 2D perovskites for highly stable photovoltaics with an 18.3% efficiency. (1st December 2022) - Ahmad, Sajjad; Lu, Ruixue; Liu, Yang; Liu, Xuan; Yang, Qing; Guo, Xin; Li, Can
Abstract: Dion-Jacobson (DJ) phase 2D layered perovskites have recently emerged as promising candidates for tackling unstable issue of perovskite solar cells (PSCs) owing to their outstanding stability compared to widely studied Ruddlesden-Popper (RP) 2D and 3D analogues. To further improve the efficiency and stability of DJ 2D PSCs, we herein report a series of cesium-doped DJ 2D perovskites (PDA)Csx (MA)3−x Pb4 I13 (PDA=1, 3-propanediammonium) and investigate Cs doping effects on material properties and device performances. The 5% Cs-doped DJ 2D PSC delivers a maximum efficiency of 18.30%, higher than the counterpart without Cs doping. Moreover, unencapsulated devices are remarkably stable, retaining ∼95% of initial efficiencies under continuous one-sun illumination for 5000 h, damp heat at 85 °C & 85% relative humidity for 240 h, and MPP tracking for 1000 h. The excellent efficiency and stability are ascribed to improved film morphology and crystallographic orientation, longer charge carrier lifetime, and reduced nonradiative recombination, induced by the Cs doping. This work demonstrates that doping Cs into DJ 2D perovskites is a facile and effective strategy towards efficient and extremely stable 2D PSCs. Graphical Abstract: ga1 Highlights: Cesium is doped into Dion-Jacobson (DJ) phase 2D perovskites for improved photovoltaic efficiency and stability. The Cs-doped DJ 2D perovskite solar cells deliver a maximum efficiency of 18.3%. Unencapsulated devices maintain ∼95% of initial efficiencies under both ISOS-D-3 and ISOS-L-1 protocols.